Analisis Visualisasi Tokoh Ajo Kawir Pada Film Seperti Dendam, Rindu Harus Dibayar Tuntas Karya Edwin Dan Eka Kurniawan - Rifa Shandhika; Jupriani Jupriani (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
There are two objectives of this research. First, analyzing the visualization of the character Ajo Kawir in the film Like Revenge, Longing Must Also Be Paid Fully. Second, to analyzing the meaning visualization of Ajo Kawir's character in the film Like Revenge, Longing Must Also Be Paid Completely. This type of research is descriptive qualitative with visual analysis method to explore various visual aspects that describe Ajo Kawir's character, including his physical appearance, facial expressions, gestures, and interactions with the environment and other characters. Data collection techniques using observation and documentation. The data analysis technique of this research is to use studies, namely Charles Sanders Pierce's Semiotics through icons, symbols, and indexes that focus on Ajo Kawir's impotence. The object of this research is the film "Like Revenge, Longing Must Also Be Paid Fully". The results of this study indicate that the impotent disease experienced by the character Ajo Kawir makes him more emotional and tries to cover it up by frequently fighting to show that he is strong. Ajo Kawir was reproached by society that people who have impotence cannot do things that are brave and strong beyond normal limits.